Risk factors for Propionibacterium acnes infection after neurosurgery: A case-control study. Issue 4 (April 2017) - Haruki, Yuto; Hagiya, Hideharu; Takahashi, Yu; Yoshida, Hideyuki; Kobayashi, Kazuki; Yukiue, Tadato; Tsuboi, Nobushige; Sugiyama, Tetsuhiro
Abstract: Propionibacterium acnes is increasingly known as a causative organism for post-neurosurgical infection; however, no clinical studies have examined the risk factors associated with P. acnes infections. Clinical data obtained from 14 cases of P. acnes infection and 28 controls infected with other pathogens were analyzed. Craniotomy, malignancy, and prolonged duration of operation were significantly associated with the onset of P. acnes infection. No fatal cases were reported.